Dietary vitamin A modifies the gut microbiota and intestinal tissue transcriptome, impacting intestinal permeability and the release of inflammatory factors, thereby influencing Aβ pathology - Wang, Zhong-Li; Pang, Shao-Jie; Zhang, Kai-Wen; Li, Peng-Yu; Li, Peng-Gao; Yang, Chun (Frontiers in Nutrition, 2024)
Background Alzheimer’s disease (AD) is an age-related neurodegenerative disorder with no effective interventions for curing or modifying its progression. However, emerging research suggests that vitamin A in the diet may play a role in both the prevention and treatment of AD, although the exact mechanisms are not fully understood. Objectives This study aims to investigate the dietary vitamin A modifies the gut microbiota and intestinal tissue transcriptome, impacting intestinal permeability and the release of inflammatory factors, thereby influencing Aβ pathology shedding light on its potential as a dietary intervention for AD prevention and treatment. Methods The APP/PS1-AD mouse model was employed and divided into three dietary groups: vitamin A-deficient (VAD), normal vitamin A (VAN), and vitamin A-supplemented (VAS) for a 12-week study. Neurobehavioral functions were assessed using the Morris Water Maze Test (MWM). Enzyme-linked immunosorbent assay (ELISA) was used to quantify levels of Diamine Oxidase (DAO), D-lactate, IL-6, IL-1β, and TNF-a cytokines. Serum vitamin A levels were analyzed via LC-MS/MS analysis. Immunohistochemical analysis and morphometry were performed to evaluate the deposition of Aβ in brain tissue. The gut microbiota of APP/PS1 mice was analyzed using 16S rRNA sequencing analysis. Additionally, transcriptomic analysis was conducted on intestinal tissue from APP/PS1 mice. Results No significant changes in food intake and body weight were observed among the groups. However, the VAD and VAS groups showed reduced food intake compared to the VAN group at various time points. In terms of cognitive function, the VAN group performed better in the Morris Water Maze Test, indicating superior learning and memory abilities. The VAD and VAS groups exhibited impaired performance, with the VAS group performing relatively better than the VAD group. Serum vitamin A concentrations differed significantly among the groups, with the VAS group having the highest concentration. Aβ levels were significantly higher in the VAD group compared to both the VAN and VAS groups. Microbial analysis revealed that the VAS and VAN groups had higher microbial diversity than the VAD group, with specific taxa characterizing each group. The VAN group was characterized by taxa such as Actinohacteriota and Desulfovibrionaceae, while the VAD group was characterized by Parabacteroides and Tannerellaceae. The VAS group showed similarities with both VAN and VAD groups, with taxa like Desulfobacterota and Desulfovibrionaceae being present. The VAD vs. VAS, VAD vs. VAN, and VAS vs. VAN comparisons identified 571, 313, and 243 differentially expressed genes, respectively, which associated with cellular and metabolic processes, and pathway analysis revealed enrichment in pathways related to chemical carcinogenesis, drug metabolism, glutathione metabolism, and immune-related processes. The VAD group exhibited higher levels of D-lactate, diamine oxidase, and inflammatory cytokines (TNF-a, IL-1β, IL-6) compared to the VAN and VAS groups. Conclusion Dietary vitamin A supplementation modulates the gut microbiota, intestinal permeability, inflammatory factors, and Aβ protein formation, offering insights into the pathogenesis of AD and potential therapeutic avenues for further exploration. This research highlights the intricate interplay between diet, gut microbiota, and neurodegenerative processes, emphasizing the importance of dietary interventions in managing AD-related pathologies.